Pelatihan manajemen referensi dan anti-plagiasi bagi mahasiswa tingkat akhir Fakultas Ushuludin, Adab dan Humaniora UIN Salatiga - Siti Muhtamiroh; Sari Famularsih; Elka Melviyana (Nur Science Institute, 2026)
This community service initiative aims to enhance the competence of final-year students at the Faculty of Ushuluddin, Adab, and Humanities, UIN Salatiga, in reference management and plagiarism checking through training on the use of Mendeley and Turnitin applications. The challenges faced by students include difficulties in systematically compiling citations and bibliographies, as well as a limited understanding of the importance of maintaining the originality of scholarly work. The activity employed a Participatory Action Research (PAR) approach, comprising stages of needs identification, training, hands-on practice, and mentoring. The training material covered reference management with Mendeley and the assessment of manuscript similarity with Turnitin. The results indicate an improvement in participants' abilities to manage citations and bibliographies automatically, check for manuscript similarity, and understand corrective measures to minimize plagiarism. Concretely, this activity helped students improve the quality of their final projects, accelerate the scholarly writing process, reduce citation errors, and raise awareness regarding academic ethics and scholarly integrity. Thus, this training and mentoring program serves as a model for sustainable enhancement of academic literacy, supporting improvements in the quality of students' scholarly work within the university environment.